(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The historical account of human beings’ association with food is in fact a prolonged narrative of their cultural and social particularities, specific and pertaining to different timelines. Food has always been and remains even today, an integral part of all cultures. Man has always been in search of new explorations of tastes, experimenting with one food or the other. From earliest times, since time immemorial, primitive men (with no difference as to modern men even with the passage of time), were preoccupied with the twin problematic concerns i. e. how to be safe and how to protect himself from the hostile environmental conditions and also how to take up the risks of eating and being eaten. Accentuated by his omnivorous drive, primitive man’s initial journeys in and around the place of his origin revolved around these incessant and relentless wanderings in search for food; a probe into what and what not is edible. Simply put, food has served as a means of man’s attempt to survive, naturally, as without food, man’s existence and survival becomes a non-debatable question. The article may be interpreted as a critical reviewing of the transitions and transformations that have complemented the growth and development of man-food affiliation; very precisely, the food-culture relationship with a special focus on Gastronomic Tourism.